Intrarenal Doppler approaches in hemodynamics: A major application in critical care - Qian, Xiaoling; Zhen, Junhai; Meng, Qingxiang; Li, Li; Yan, Jing (Frontiers in Physiology, 2022)
The treatment of severe cases usually requires multimodality hemodynamic monitoring approaches, particularly for tissue and organ perfusion tracking. Currently, only a few studies have investigated renal perfusion status at the bedside. Ultrasound has become increasingly utilized to guide the hemodynamic management of severe patients. Similarly, intrarenal Doppler (IRD) is widely used to assess renal perfusion from both the intrarenal artery and vein perspectives. The renal resistive index (RRI), which reflects the renal arterial blood flow profile, is often applied to predict the reversibility of renal dysfunction and to titrate hemodynamic support. Intrarenal venous flow (IRVF) patterns and the renal venous stasis index (RVSI), which reflects the intrarenal vein blood flow profile, are now being used to assess intravenous congestion. They may also be useful in predicting the risk of acute kidney injury and avoiding fluid overload. IRD can provide diverse and supplemental information on renal perfusion and may help to establish the early diagnosis in severe patients. This review focused on the specific operational methods, influencing factors, and applications of IRD in hemodynamics.